Urinary type II collagen C-telopeptide levels are increased in patients with rapidly destructive hip osteoarthritis. Issue 10 (12th September 2003) - Garnero, P; Conrozier, T; Christgau, S; Mathieu, P; Delmas, P D; Vignon, E
Abstract : Objective: To compare type II collagen degradation using a new urinary specific marker in patients with rapidly destructive and those with slowly progressive hip OA. Methods: Twelve patients with rapidly destructive and 28 patients with slowly progressive hip OA were included in a prospective, cross sectional case-control study. Urinary levels of C-terminal crosslinking telopeptide of collagen type II (CTX-II) as a marker of cartilage degradation were measured by an ELISA, and urinary free deoxypyridinoline (free DPD), a marker of bone resorption, was measured by high performance liquid chromatography. One x ray evaluation of the hips and urine samples was made in all patients when the diagnosis of OA was established. Results: Patients with hip OA had higher mean (SD) urinary CTX-II levels than 65 healthy age matched controls (492 (232) v 342 (141), p<0.001), but no significant difference was seen for urinary free DPD (p=0.30). Increased urinary CTX-II, but not urinary free DPD, correlated significantly with decreased minimum joint space width assessed by radiograph of the hip. Mean urinary CTX-II levels were significantly higher in patients with rapidly progressive OA than in the slowly progressive group (612 (218) v 441 (221), p=0.015), whereas no significant difference of urinary free DPD was seen between the two groups (p=0.55). Conclusion: Patients with hip OA have increased CTX-II degradation as assessed by a new urinary marker. Increased urinary CTX-II levels are associated with rapidly destructive disease, suggesting that this marker might be useful in identifying patients with hip OA at high risk for rapid progression of joint damage.